1976
DOI: 10.1021/ja00436a035
|View full text |Cite
|
Sign up to set email alerts
|

Polar radicals. 9. Kinetics and mechanism of the vapor-phase bromination of 1-bromobutane

Abstract: The vapor-phase photobromination of 1-bromobutane with molecular bromine (5:1) yields 11 products resulting from direct substitution or the elimination of a bromine atom from the 1 -(bromomethyl)propyl radical. The 1 -butene resulting from elimination undergoes addition, and allylic substitution and addition to yield polyhalogenated materials. The major portion of the bromine (65% ) produced 1,2,3-tribromobutane and 1,2,3,4-tetrabromobutane. Bromination with bromine-81 produced isotopically enriched products w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The conclusions from these observations are identical with those reached for the brornination of 1 -bromobutane under comparable conditions (20). It can be concluded that the a-bromoalkyl radical is stable under these conditions.…”
Section: Discussion and Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The conclusions from these observations are identical with those reached for the brornination of 1 -bromobutane under comparable conditions (20). It can be concluded that the a-bromoalkyl radical is stable under these conditions.…”
Section: Discussion and Resultssupporting
confidence: 83%
“…Such an allylic bromination pathway could account for the 1,2,3-tribromobutane, the unsaturated bromides, and the saturated polyhalogenated materials. A similar mechanism was proposed for the vapor phase bromination of 1-bromobutane (20). The fate of the p-bromoalkyl radical can be affected by either the temperature of the system or the concentration of the transfer agents.…”
Section: Discussion and Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…4 Studies on the bromination of ~h b r o b u t a n e (5), and 1-br~mobutane (6) in the several model compounds, cyclohexane (I), 1-vapor phase, where neither the cage reaction nor the transfer reaction with hydrogen tribromide are im- 'Author to whom correspondence may be addressed.…”
Section: Introductionmentioning
confidence: 99%